REFORMULATION OF BUMN REGULATIONS: REINVENTION STRATEGY FOR BUMN EMPOWERMENT FOR PEOPLE WELL-BEING - Gunawan Nachrawi (Awang Long Law Review, 2021)
State-Owned Enterprises (BUMN), which is one of the concrete manifestations of Article 33 of the 1945 Constitution, has a strategic position for improving the welfare of the people. However, the extent to which BUMN is able to become a state tool to improve the welfare of the people and the nation depends on the level of efficiency and performance of the BUMN itself. Efforts to reformulate BUMN arrangements are needed so that the objectives of BUMN reinventing in the form of restructuring, provocation and privatization can run well so that efficiency efforts of BUMN that are globally competitive can be carried out properly. Currently there are 107 SOEs, previously in 2010 there were 142 SOEs. The problem is, what is the reinvention strategy for empowering BUMN for the welfare of the people? Analysis and reformulation of Law Number 19 of 2003 concerning State-Owned Enterprises, especially the regulation regarding the efficiency and effectiveness of BUMN as a fundamental and sustainable public company. Efforts to streamline the number of BUMNs from 107 to 40 companies with 12 holding companies throughout Indonesia should be regulated in advance in law. Matters that need to be regulated include orientation, vision and mission, strategy, merger, consolidation, acquisition, dissolution, and matters relating to reinvention including making BUMN go public and world class.